United States of America. Significant achievements 2015 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in the United States during 2015 are identified, with respect to the needs and interests of the country, strengthening issues such as sustainability, biotechnology, biosafety, public policies, trade, risk management, family farming, agribusiness, innovation, technology, food security and resilience against climate change. Likewise, work was done on productivity, on the development of rural life, livestock systems, management of natural resources. Finally, it was provided in technical cooperation, in the use of the Codex Alimentarius and in value chains.